1997
DOI: 10.1108/eum0000000007201
|View full text |Cite
|
Sign up to set email alerts
|

Parallel computing in information retrieval – an updated review

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. The progress of parallel computing in Information Retrieval (IR) is reviewed. In particular we stress the importance of the motivation in using parallel computing for Text Retrieval. We analyse parallel IR systems using a classification due to Rasmussen [1] and describe some parallel IR systems. We give a description of the retrieval models used in parallel Information PermanentProcessing.. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

1999
1999
2019
2019

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 62 publications
(179 reference statements)
0
9
0
3
Order By: Relevance
“…In the area of IR systems, several approaches have been developed that show scalability [2][3][4][5][6][7][8]. However, little work has been done with extending the use of the information retrieval to be applied to the data analytics.…”
Section: Related Workmentioning
confidence: 99%
“…In the area of IR systems, several approaches have been developed that show scalability [2][3][4][5][6][7][8]. However, little work has been done with extending the use of the information retrieval to be applied to the data analytics.…”
Section: Related Workmentioning
confidence: 99%
“…This is called document-id partitioning. [39] Each query is broadcast to all nodes in the cluster and each of them processes the query over the index for the piece of the collection for which they are responsible. The nodes may need to communicate with each other to exchange global statistical information such as df values.…”
Section: Types Of Parallelismmentioning
confidence: 99%
“…These partitions are fragmented across physical disks. A fuller discussion of these partitioning methods can be found in (Jeong & Omiecinski, 1995;MacFarlane et al, 1997) and an example can be found in appendix 1. Two types of index build methods are used: Local and Distributed.…”
Section: Introductionmentioning
confidence: 99%